Круговійчасті інфузорії (Ciliophora, Peritrichia) в аеротенках очисних споруд м. Житомира - Константиненко, Л.А. (Вестник зоологии, 2007)
В активном иле аэротенков очистных сооружений г. Житомира обнаружены 19 видов перитрих. Восемь из них — новые для фауны Украины. Приведены диагнозы и рисунки новых для региона видов. 19 species of Peritrichia were found in the activated sludge of activated sludge tank in the sewage treatment plant from Zhytomyr. Eight of them are new for Ukrainian fauna. The diagnoses and pictures of the new for the region species are given.